Extracellular vesicle-associated microRNA-30b-5p activates macrophages through the SIRT1/ NF-κB pathway in cell senescence - Xiao, Yu; Liang, Jiaqi; Witwer, Kenneth W.; Zhang, Ying; Wang, Qian; Yin, Hang (Frontiers in Immunology, 2022)
Chronic inflammation is widely observed in aging, but it is unclear whether extracellular vesicles (EVs) play a role in chronic disease-associated senescence. In our study, LC/MS profiling revealed that senescent cell derived EVs (SEN EVs) activate the immune response pathways of macrophages. Significantly more EVs were found in the supernatant of SEN than of control (CON) cell cultures, and SEN EVs were enriched in miR-30b-5p, which directly target sirtuin1 (SIRT1). In vitro, we found that SEN EVs treatment resulted in increased cellular levels of interleukin-1β (IL-1β) and IL-6 and decreased the level of SIRT1. These increased cytokine could be reversed by SIRT1 activation and miR-30b-5p inhibition. Furthermore, miR-30b-5p significantly increased with age in both mouse liver tissue and EVs harvested from the tissue, with differences in EVs observed both earlier and in the later magnitude of aging. Western blot and qPCR proved that miR-30b-5p downregulated the level of SIRT1 in mouse macrophages. Collectively, we propose that EVs carrying miR-30b-5p from SEN cells can induce chronic inflammation through macrophage activation. This occurs through the downregulation of SIRT1 and the corresponding activation of NF-κB pathways that enhance pro-inflammatory cytokine production. Collectively, these results demonstrate that EVs carrying pro-inflammatory signals are released by SEN cells and then activate immune cells in the SEN microenvironment, changing the inflammatory balance. Our results also explain why inflammation increases with age even though SEN cells can be immediately eliminated under rigorous immune surveillance.